2016
DOI: 10.1093/jisesa/iew047
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Imaging As a Method of Studying Tsetse Fly (Diptera: Glossinidae) Pupal Development

Abstract: Near infrared (NIR) photography and video was investigated as a method for observing and recording intrapuparial development in the tsetse fly Glossina palpalis gambiensis and other Muscomorpha (Cyclorrhapha) Diptera. We showed that NIR light passes through the puparium, permitting images of the true pupae and pharate adult to be captured. Various wavelengths of NIR light from 880 to 1060 nm were compared to study the development of tsetse fly pupae from larviposition to emergence, using time-lapse videos and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Previous studies have shown the potential of imaging systems in entomological studies. Moran and Parker (2016) used NIR imaging to study the intrapupal development of Tsetse fly (Diptera: Glossinidae), and to distinguish males from females several days before emergence. Hyperspectral imaging (HSI) spectroscopy was evaluated for determining the age and species of blowfly (Diptera: Calliphoridae) (Voss, Magni, Dadour, & Nansen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the potential of imaging systems in entomological studies. Moran and Parker (2016) used NIR imaging to study the intrapupal development of Tsetse fly (Diptera: Glossinidae), and to distinguish males from females several days before emergence. Hyperspectral imaging (HSI) spectroscopy was evaluated for determining the age and species of blowfly (Diptera: Calliphoridae) (Voss, Magni, Dadour, & Nansen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A higher female to male wasp ratio is desirable for achieving higher parasitism because only females can oviposit eggs onto the host larvae. A previous study showed that the gender of the tsetse fly ( Glossina palpalis gambiensis ) (Diptera: Glossinidae) could be identified at the pupal stage using NIR imaging . This study did not consider determining the gender of larvae in cocoons, however, we assume that the MS imaging system would have a similar ability for the studied parasitoid.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the identification of rice weevil species, Sitophilus (Coleoptera: Curculionidae), used an MS imaging approach by selecting only images of the useful wavelengths from an originally visible/NIR hyperspectral image . A similar approach was used to study pupal development in the tsetse fly ( Glossina palpalis gambiensis ) (Diptera: Glossinidae) using NIR hyperspectral imaging . These studies involving hyperspectral imaging have highlighted the MS imaging system as a prospective technology with practical application, primarily due to a significant reduction in image size and rapid analysis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations